OC-066 A preliminary study of neurostimulation based interventions in the treatment of chronic dysphagia post-stroke. (23rd September 2015) - Michou, E; Mistry, S; Jefferson, S; Singh, S; Hamdy, S
Abstract : Introduction: Oropharyngeal dysphagia after stroke has an incidence up to 45% and when chronic, leads to increased risk of institutionalisation and death in the long term. Pharyngeal electrical stimulation (PES), 1 repetitive transcranial magnetic stimulation (rTMS)2 and paired associative stimulation (PAS)3 are three neurostimulation techniques developed to increase cortical excitability of pharyngeal motor cortex, with therapeutic potential. However the effects of these techniques on chronic but stable swallowing problems in stroke patients remain unknown. We therefore investigated the effects of these interventions in stroke patients with dysphagia persisting for >6 weeks. Methods: In 12 dysphagic stroke patients (69±9 years (mean±SD), 79±25 weeks post-stroke (mean±SD), 6 left, 5 right hemispheric, 1 undetermined) pharyngeal electromyographic responses were recorded using an intraluminal catheter after the application of single TMS pulses over pharyngeal motor cortex, in order to measure cortico-bulbar excitability before, immediately and 30 minutes after real and sham applications of either: a) PES (10 mins of 5 Hz), b) rTMS (250 repeated TMS pulses at 5 Hz), or c) PAS (10 mins of repeated pairs of pharyngeal and TMS pulse every 20 s). In nine subjects, swallowing performance and safety (aspiration-penetration scores, APs) were assessed with videofluoroscopy before and after both real and sham neurostimulation techniques. Results: Compared to sham, the application of all neurostimulation interventions showed a significant increase in cortical excitability in the unaffected hemisphere by 54%±17% (mean±SEM) immediately post (repeated measures ANOVA p<0.001, Time*Intervention p=0.005), not observed in the affected hemisphere (p=0.12). In addition, after active neurostimulation, APs were reduced by −14%±6% (mean±SEM) compared to sham (Wilcoxon's test, p=0.05). Moreover, the delay between the oral and pharyngeal phases of swallowing, important for swallowing safety, was shortened by −56%±13% (mean±SEM) after real neurostimulation (Wilcoxon's test, p=0.01) compared to sham. There was no consistent difference in cortical or swallowing response between the interventions. Conclusion: These preliminary results show that neurostimulation interventions have beneficial neurophysiological and behavioural effects in chronic stroke patients with dysphagia, increasing cortical excitability and improving swallowing safety. These findings provide support for neurostimulation being a useful adjunct in swallowing rehabilitation, even in chronic neurologic illness, and lay the foundation for further clinical trials of these forms of intervention.